Post‐infectious bronchiolitis obliterans and mannose‐binding lectin insufficiency in Argentinean children. Issue 6 (4th May 2015) - Giubergia, Verónica; Salim, Maximiliano; Fraga, Jesica; Castiglioni, Nicolás; Sen, Luisa; Castaños, Claudio; Mangano, Andrea
Abstract Background and objective Post‐infectious bronchiolitis obliterans (PIBO) is a severe disorder following acute lower pulmonary infection in young children, especially caused by adenovirus. Mannose‐binding lectin (MBL) deficiency arising from polymorphisms in the coding and non‐coding region on the MBL2 gene has been associated with more frequent and severe respiratory infections. Our aim was to evaluate the influence of MBL variants in the susceptibility and evolution of children with PIBO. Methods One hundred eleven children with PIBO diagnosis were studied. The coding A, B, D and X promoter variants of MBL2 gene were assessed by PCR‐RFLP. B and D alleles were pooled as O. The combined genotypes A/A and YA/O were grouped as sufficient MBL (sMBL), and O/O and XA/O as insufficient MBL (iMBL) groups. To evaluate the frequency of MBL2 polymorphisms in the general population, we studied DNA samples from 127 healthy donors from the blood bank of the hospital (control group). Results iMBL variants were significantly more frequent in PIBO children compared with controls (21.6% vs 10.2%, P = 0.01). PIBO patients with iMBL required intensive care unit (P = 0.001) and mechanical assistance at the moment of viral injury (P = 0.001) more frequently than those with sMBL. Conclusions Insufficiency of MBL was more common in PIBO children than in healthy controls. This genetic condition was significantly associated with more severe initial disease, illustrating the relevance of innate immune defence factors prior to the maturation of the adaptative immune system.